Beyond the technological chain - Petr Květina; Louise Gomart; Richard Thér; Klára Neumannová (Archeologické Rozhledy, 2017)
Formal and technological attributes of pottery mirror potters’ habitus, actions, and decisions inhibited or stimulated by users of pottery. The variability of these attributes in time and space reflects networks of producers embedded in a complex social network. But how the knowledge of pottery manufacturing processes can be used to gain more accurate understanding of the society behind the “chaînes opératoires” when the basis for the interpretation is archaeological evidence? Can archaeologists reach reliable picture on relations between pottery technology and society? Can the interpretations be built on testable hypotheses? Those are painful issues accompanying all the archaeological attempts to understand variability and changes in pottery technology, the issues that motivate the main theme of the thematic issue of Archeologické rozhledy: the pursuit of archaeologists to integrate pottery technology analysis to the complex interpretation of the Neolithic societies.